HEPATOPROTECTIVE POTENTIAL OF MALABAR TAMARIND (Garcinia gummi-gutta) FRUIT-RIND EXTRACT IN ACETAMINOPHEN-INDUCED TOXICITY THROUGH MODULATION OF CYP2E1 GENE EXPRESSION IN HEPATIC CELLS OF WISTAR RATS (Applied Biological Research, 2023)
The present study was aimed to assess the hepatoprotective effect of  ethanolic extract of Garcinia gummi-gutta (GGE) fruit rind on  acetaminophen-induced toxicity in a rat model and to explore the possible  mechanism of action by assessing hepatic histopathology, serum biochemical parameters and expression of CYP2E1 gene in hepatic cells. The  group I and 11 animals served as normal control and hepatotoxic control  group, respectively; while group III, IV and V were administrated with  GGE fruit-rind extract @ 50, 100 & 200 mg kg-1 orally, respectively, for 10  days. The group VI (positive control) received drug silymarin @ 100 mg kg-1 day-1 orally for 10 days. Hepatotoxicity was induced by single oral  administration of acetaminophen (2 g kg-1) on 8th day. The results revealed  that the extract produced dose-dependent hepatoprotective effect against  acetaminophen-induced hepatic damage by improving the serum bio chemical profile towards the normal range. Histopathology of liver showed that pretreatment with fruit-rind extract attenuated the toxicant-induced  hepatocellular necrosis and enhanced the regeneration of hepatic cells. The  hepatic expression level of CYP2E1 gene was found down-regulated in a  dose dependent manner in extract-treated group as compared to the normal control group. The study revealed remarkable hepatoprotective  effect of GGE in acetaminophen-induced toxicity in rats through  regeneration of hepatic cells and by decreasing the formation of reactive  metabolite, NAPQ1 by modulation of CYP2E1 gene expression in liver.
Keywords: Acetaminophen; CYP2E1; Garcinia gummi-gutta; liver; Wistar rats